CIRCUITI COMMERCIALI E NON COMMERCIALI DEL SAPERE (2) - VITIELLO, Nato Defense College, Roma , Giuseppe (BIBLIOPOLIS, 2020)
The article – the second of a three-article series devoted to scholarly communication chains – explores some of the integrations between the commercial and non-commercial sectors. It examines how, and why, Google Books “ventures” together with OCLC and the paradox of including open access resources in commercial publishing websites. “Freeconomics” turns upside down traditional economics but also explains why digital goods, costly though they are, may be distributed at no cost for consumers. By giving away their services and products, Google and commercial publishers acquire a long-lasting competitive advantage over their competitors, as their markets are no longer based on resource scarcity. If this is good news for customers, it is not for libraries. They start losing the rationale for being acknowledged as the only non commercial scholarly communication chain. This trend also shows the power of library cooperative agencies, whose developments work along a business model that is no longer dependent on libraries as institutions.